A Qualitative Case Study of How Finnish Teachers Transform Grade 2 English Reading Subject into Students’ Imaginative and Character-building Adventures - Tholchah, Muchammad; Bhattarai, Devi Prasad (EduBase : Journal of Basic Education, 2025)
Finland’s consistently high performance in international assessments such as PISA has drawn global attention to its early educational practices, particularly in literacy instruction. Objective: This study explores the role of teachers in English reading subject in lower-grade Finnish classrooms, emphasizing how literacy education extends beyond technical skill acquisition. Novelty: This integrated approach positions literacy as both a cognitive and socio-emotional enterprise, central to holistic learner development. Methods: Using a qualitative case study design, data were collected through interviews with a teacher, a parent, and a Grade 2 student, complemented by analysis of instructional materials. Results: Framed by Pedagogical Content Knowledge (PCK), the findings demonstrate that Finnish teachers use English reading subject not only to develop academic skills such as fluency and comprehension but also to stimulate imagination and cultivate positive character values. Conclusions: While the small sample limits generalizability, the study offers critical insights for advancing literacy pedagogy and highlights directions for cross-cultural and longitudinal research.